Optimal Design and Installation of Solar Rooftop for Thai government building - Jedsada Chaishome; Navaphattra Nunak; T. Suesut (My University, 2025)
This research presents an approach for installing grid-connected solar cells on the rooftops of a prototype building in Thailand to offset electricity consumption, aligning with TOU electricity pricing. It includes design methods, energy-saving calculations, and illustrates the savings from solar cell installation over a one-year period, without accounting for solar cell deterioration or system loss charges. The study compares the concept of installing solar cells on the rooftop based on the building’s electricity usage characteristics, distinguishing between installing solar cells across the entire rooftop area and according to the building’s electricity usage behavior during daytime and working days, ensuring minimal electricity remains while still being sufficient for use. Furthermore, it calculates the comparison before and after installation to provide information for rooftop installation on the prototype building. The research results indicate that installing solar cells across the entire rooftop area can save electricity costs up to 550,000 THB per year.
Keywords: Architecture and Computational Design; Building Energy and Comfort Optimization